2020
DOI: 10.2147/cmar.s260150
|View full text |Cite
|
Sign up to set email alerts
|

<p>Construction and Comprehensive Analysis of a ceRNA Network to Reveal Potential Novel Biomarkers for Triple-Negative Breast Cancer</p>

Abstract: Background: Triple-negative breast cancer (TNBC) is the most common and aggressive type of breast cancer with an unfavourable outcome worldwide. Novel therapeutic targets are urgently required to explore this malignancy. This study explored the ceRNA network and the important genes for predicting the therapeutic targets. Methods: It identified the differentially expressed genes of mRNAs, lncRNAs and miRNAs between TNBC and non-TNBC samples in four cohorts (TCGA, GSE38959, GSE45827 and GSE65194) to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…To date, the four pyroptosis-related lncRNAs in our model have not yet been studied in bladder cancer. However, survival analysis performed by Ma et al indicated that lncRNA AC124312.3 was notably correlated with the OS of triple-negative breast cancer patients and may be a promising therapeutic target [ 24 ]. Moreover, the upregulation of lncRNA AC007128.1 is associated with the poor prognosis of esophageal squamous cell carcinoma patients [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the four pyroptosis-related lncRNAs in our model have not yet been studied in bladder cancer. However, survival analysis performed by Ma et al indicated that lncRNA AC124312.3 was notably correlated with the OS of triple-negative breast cancer patients and may be a promising therapeutic target [ 24 ]. Moreover, the upregulation of lncRNA AC007128.1 is associated with the poor prognosis of esophageal squamous cell carcinoma patients [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this is the first study to provide a risk sampling model for osteosarcoma based on three long RNAs with prognostic relevance linked to pyroptosis. Bioinformatics study has previously shown RPARP-AS1 and AC124312.3 in breast cancer [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] LncRNAs act as ceRNA that play an important role in cellular biological processes and tumorigenesis. [ 15 ] The ceRNA network has been constructed in different types of cancers including gastric cancer, [ 16 ] tongue squamous cell carcinoma, [ 17 ] hepatocellular carcinoma, [ 18 ] breast cancer, [ 19 ] and so on. In 2018, Zhang et al constructed a lncRNA-associated ceRNA network in colon cancer using the TCGA database to identify biomarkers.…”
Section: Discussionmentioning
confidence: 99%